Arsenic exposure induces a bimodal toxicity response in zebrafish. (15th October 2021) - Coral, Jason A.; Heaps, Samuel; Glaholt, Stephen P.; Karty, Jonathan A.; Jacobson, Stephen C.; Shaw, Joseph R.; Bondesson, Maria
Abstract: In toxicology, standard sigmoidal concentration-response curves are used to predict effects concentrations and set chemical regulations. However, current literature also establishes the existence of complex, bimodal concentration-response curves, as is the case for arsenic toxicity. This bimodal response has been observed at the molecular level, but not characterized at the whole organism level. This study investigated the effect of arsenic (sodium arsenite) on post-gastrulated zebrafish embryos and elucidated effects of bimodal concentration-responses on different phenotypic perturbations. Six hour post fertilized (hpf) zebrafish embryos were exposed to arsenic to 96 hpf. Hatching success, mortality, and morphometric endpoints were evaluated both in embryos with chorions and dechorionated embryos. Zebrafish embryos exhibited a bimodal response to arsenic exposure. Concentration-response curves for exposed embryos with intact chorions had an initial peak in mortality (88%) at 1.33 mM arsenic, followed by a decrease in toxicity ( 20% mortality) at 1.75 mM, and subsequently peaked to 100% mortality at higher concentrations. To account for the bimodal response, two distinct concentration-response curves were generated with estimated LC10 values (and 95% CI) of 0.462 (0.415, 0.508) mM and 1.69 (1.58, 1.78) mM for the 'low concentration' and 'high concentration' peaks, respectively. Other phenotypic analyses, including embryo length, yolk and pericardial edema all produced similar concentration-response patterns. Tests with dechorionated embryos also resulted in a bimodal toxicity response but with lower LC10 values of 0.170 (0.120, 0.220) mM and 0.800 (0.60, 0842) mM, respectively. Similarities in bimodal concentration-responses between with-chorion and dechorionated embryos indicate that the observed effect was not caused by the chorion limiting arsenic availability, thus lending support to other studies such as those that hypothesized a conserved bimodal mechanism of arsenic interference with nuclear receptor activation. Graphical abstract: Image 1 Highlights: Zebrafish embryos exhibit bimodal concentration-responses to arsenic exposure. Bimodal responses extend to mortality, hatching, and numerous phenotypic endpoints. Removal of the chorion does not remove the bimodal toxicity response. Results suggest arsenic MOA is tied to complex interactions with nuclear receptors. Abstract : A bimodal concentration-response to arsenic was identified across numerous phenotypes in zebrafish. The effect persisted with chorion removal, suggesting that other mechanisms than chorion protection mediate the bimodal response.